2010
DOI: 10.1007/s10546-010-9529-5
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Oxygen Isotope Composition of Evapotranspiration Using Eddy Covariance

Abstract: The oxygen isotope composition of evapotranspiration (δ F ) represents an important tracer in the study of biosphere-atmosphere interactions, hydrology, paleoclimate, and carbon cycling. Here, we demonstrate direct measurement of δ F based on the eddy-covariance and tunable diode laser spectroscopy (EC-TDL) techniques. Results are presented from laboratory experiments and field measurements in agricultural ecosystems. The field measurements were obtained during the growing seasons of 2008 and 2009. Water vapou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 28 publications
4
64
0
Order By: Relevance
“…The typical vapor equilibrium takes about 24 h. Over the past decade, a revolutionary change in water isotope measurements has seen the appearance of spectroscopy based isotope instruments capable of making continuous measurements of water vapor isotopic compositions. This new type of instruments does not usually require pretreatment and have precisions similar to traditional cryogenic based mass spectrometry methods (Lee et al, 2005;Wen et al, 2008;Wang et al, 2009d;Griffis et al, 2010). Recent research has indicated that plant derived volatile compound induced spectral contamination in leaf and stem water measurements could affect the accuracy of water stable isotopic compositions significantly (West et al, 2010;Zhao et al, 2011), limiting the application of spectroscopy-based method to plant sample measurements.…”
Section: Evapotranspiration Partitionmentioning
confidence: 99%
“…The typical vapor equilibrium takes about 24 h. Over the past decade, a revolutionary change in water isotope measurements has seen the appearance of spectroscopy based isotope instruments capable of making continuous measurements of water vapor isotopic compositions. This new type of instruments does not usually require pretreatment and have precisions similar to traditional cryogenic based mass spectrometry methods (Lee et al, 2005;Wen et al, 2008;Wang et al, 2009d;Griffis et al, 2010). Recent research has indicated that plant derived volatile compound induced spectral contamination in leaf and stem water measurements could affect the accuracy of water stable isotopic compositions significantly (West et al, 2010;Zhao et al, 2011), limiting the application of spectroscopy-based method to plant sample measurements.…”
Section: Evapotranspiration Partitionmentioning
confidence: 99%
“…Calibration of water vapour analysers is done, for example, using a liquid water injector ("dripper") into a flow of dry air (Lee et al, 2005;Wen et al, 2008;Baker and Griffis, 2010;Griffis et al, 2010;Sturm and Knohl, 2010). In addition, a heated vaporisation system is used wherein the liquid standard is completely vaporized without fractionation.…”
Section: Instrument Accuracy and Calibrationmentioning
confidence: 99%
“…However, to measure the source/sink signature properly near the land surface, one should interface the isotopic analyser with plant (Barbour et al, 2007;Barthel et al, 2011) and soil chambers (e.g. Wingate et al, 2010a, b) and deploy it in the gradientdiffusion mode either over the vegetation (Griffis et al, 2004) or over the soil surface inside the canopy (Santos et al, 2010), or combine it with a sonic anemometer for direct eddy covariance measurement of isotopic fluxes (Lee et al, 2005;Griffis et al, 2008Griffis et al, , 2010 or landscape scale measurements in high elevation or airborne conditions (e.g. Tuszon et al, 2010).…”
Section: High Instrument Precision At Short Detection Intervalsmentioning
confidence: 99%
“…Even if measurements are taken every second, an integration time of several minutes up to 1 h is required during field monitoring, in order to obtain a precision better than 0.5 ‰ for δ 13 C. At the moment, the LGR CCIA-EP does not allow us to investigate faster temporal dynamics, such as high-frequency data required for eddy covariance [22]. The eddy covariance (also known as eddy correlation or eddy flux) is a key atmospheric measurement technique to measure and calculate vertical turbulent fluxes within atmospheric boundary layers.…”
Section: Dealing With the Temporal Instability Of The Analyzermentioning
confidence: 99%